Early markers for cerebral palsy: insights from the assessment of general movements. (November 2012) - Einspieler, Christa; Marschik, Peter B; Bos, Arend F; Ferrari, Fabrizio; Cioni, Giovanni; Prechtl, Heinz FR
Overt clinical symptoms of cerebral palsy do not emerge before a child is at least half a year old. Among the most reliable early markers for cerebral palsy are abnormal 'general movements' (GMs). Two specific abnormal GM patterns predict cerebral palsy: cramped-synchronized GMs (during preterm and term age), which lack the usual smoothness and fluent character; and limb and trunk muscles contract almost simultaneously and relax almost simultaneously. In addition, the absence of so-called fidgety movements at 3–5 months post-term age. Fidgety movements are small movements of the neck, trunk and limbs in all directions and of variable acceleration. Beside a high sensitivity (>91%) and specificity (>81%), the assessment of GMs is quick, nonintrusive and easy to acquire.